Biomechanical Modelling of the Foot to Improve Segment Power Estimates in the Vertical Jump - Carmichael, Wendy (My University, 1995)
The present study develops a foot model to improve segment power estimates in the vertical jump. Modifications to the traditional foot model included the addition of a forefoot segment to allow for power flow across the metatarsal-phalangeal joint, and a re-definition of the ankle joint position to decrease foot segment length variability. The foot model was evaluated by comparison of the total segment power (TSP) with the rate of change of energy (RCE) of the foot segment. Pearson's correlation coefficients and percent root mean square (% RMS) error were used to compare curves.
Power flow analysis was performed on a counter-movement jump (CMJ) and a squat jump (SQJ) for each of 8 male and 8 female subjects. Both a 4-Link and a 5-Link, sagittal plane, link-segment model were used to calculate the joint and muscle powers.
The combination of both modifications to the traditional foot model (i.e. 5-Link(ankle) model), resulted in dramatic improvements for the match between the TSP and RCE. When comparing the traditional model with the 5-Link(ankle) model for the CMJ, correlation coefficients improved from -0.46 to 0.92 for the male group and from -0.50 to 0.77 for the female group. The %RMS error decreased from 380.5% to 35.4% for the male group and from 466.9% to 71.6% for the female group. SQJ improvements were similar.
Ankle joint position re-definition succeeded in compensating for foot segment length changes in most cases, and indicates that a single point can be located to act as a hinge joint between the foot and leg segments throughout the vertical jump motion. Improvements associated with the addition of a forefoot segment to the traditional linksegment model indicate that substantial power flow occurs through the metatarsal-phalangeal joint during vertical jump motions.
Keywords: biomechanical; foot; segment power; vertical jump